2017
DOI: 10.1590/0034-7167-2016-0194
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety and nursing: interface with stress and Burnout Syndrome

Abstract: Objective: To analyze studies on stress, Burnout Syndrome, and patient safety in the scope of nursing care in the hospital environment. Method: This was an integrative literature review. Data collection was performed in February 2016 in the following databases: Medical Literature Analysis and Retrieval System Online - PubMed/MEDLINE, Latin American and Caribbean Literature in Health Sciences - LILACS. Results: Ten scientific productions were selected, which listed that factors contributing to stress and Burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
(22 reference statements)
0
25
0
24
Order By: Relevance
“…However, a study conducted in a private hospital in Minas Gerais found that 53.66% of professionals who participated had another registered job, but there was not a significant relation between this fact and the score regarding the atmosphere of safety (10) . The existence of only one registered job may be seen as a factor that contributes to the safety of the patients, since work overload negatively interferes in the assistance provided, favoring the occurrence of adverse events (15) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted in a private hospital in Minas Gerais found that 53.66% of professionals who participated had another registered job, but there was not a significant relation between this fact and the score regarding the atmosphere of safety (10) . The existence of only one registered job may be seen as a factor that contributes to the safety of the patients, since work overload negatively interferes in the assistance provided, favoring the occurrence of adverse events (15) .…”
Section: Discussionmentioning
confidence: 99%
“…33 Aspect resulting in the presence of Burnout Syndrome in nursing professionals and which, in parallel, has repercussions on lack of safety in the care given to people. 34 In view of the robust scientific findings presented, strategies to promote the physical activity of the universe investigated extrapolate the labor gymnastics, to contemplate a larger daily workload, to be performed outside working hours (Article 19 in Table 1). Contemplation that in addition to contributing to reducing the levels of work stress, attenuates possible interpersonal conflicts due to problems in the organization of work, gaps in the knowledge of workers, among others (Article 17 in Table 1).…”
Section: Given the Potential Benefits And The Limited Risk Of Offerinmentioning
confidence: 99%
“…Em estudos anteriores, que objetivaram investigar a relação existente entre o estresse ocupacional e a fadiga com a SB, são reportadas correlações altas e significativas em todos os fatores, revelando que quanto maior for o nível de fadiga e estresse no trabalho, maior o índice de SB (Brandão, Serpa, Rosaldo, & Weingerg, 2014;Dalri, Silva, Mendes, & Robazzi, 2014). Nesse contexto, Rodrigues, Santos & Sousa (2017) realizaram uma revisão integrativa de estudos sobre a SB e o estresse em profissionais no ambiente hospitalar, indicando que o estresse e a SB acarretam uma vulnerabilidade associada a falta de apoio organizacional. Ademais, reporta-se ainda que a fadiga e o estresse no trabalho podem produzir uma menor qualidade no atendimento do paciente, intenção de sair do trabalho e maior frequência de erros clínicos (Farias, Araújo, Oliveira, Silva, & Miranda, 2017;Rodrigues et al, 2017).…”
Section: Estresse Ocupacionalunclassified
“…Nesse contexto, Rodrigues, Santos & Sousa (2017) realizaram uma revisão integrativa de estudos sobre a SB e o estresse em profissionais no ambiente hospitalar, indicando que o estresse e a SB acarretam uma vulnerabilidade associada a falta de apoio organizacional. Ademais, reporta-se ainda que a fadiga e o estresse no trabalho podem produzir uma menor qualidade no atendimento do paciente, intenção de sair do trabalho e maior frequência de erros clínicos (Farias, Araújo, Oliveira, Silva, & Miranda, 2017;Rodrigues et al, 2017).…”
Section: Estresse Ocupacionalunclassified